Modeling and Analysis of the Dynamic Response of an Off-Grid Synchronous Generator Driven Micro Hydro Power System - Ali, Waqas; Farooq, Haroon; Rasool, Akhtar; Sajjad, Intisar Ali; Zhenhua, Cui; Ning, Lin (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
This paper models and analyses the dynamic response of a synchronous generator driven off-grid micro hydro power system using Simulink tool of MATLAB software. The results are assessed from various perspectives including regulation through no load to full load and overload scenarios under normal and abnormal operating conditions. The investigation under the normal conditions of no load, linearly changing load and full load divulges that the system operates in a satisfactory manner as generator voltage and frequency remain approximately constant at 1 pu. However, at full load generator voltage and frequency drop 3% and 0.5% respectively from its nominal values but remain within prescribed standard IEC limits. The results also expose that the abnormal conditions produced by abrupt changes in load, system faults and severe overload, cause the unwonted variations in the magnitude of generator parameters. Moreover, the study reveals that the system stability significantly enhances when the system is run at full load because the regulation time to fix the variations in the generator parameters; except input mechanical power; decreases, e.g. from 4.1 sec to 0.8 sec for generator voltage, with the increase in the loading from quarter to full load respectively at unity power factor. Further, it is also observed that the regulation time rises, e.g. from 0.8 sec to 1.3 sec for generator voltage, with the reduction in load power factor from unity to 0.8, respectively. Thus, proper protection, to cater for increased fault current at full load and power factor correction must be provided to improve the system stability and protection. Furthermore, it is also concluded that the over loading in any case should be strongly avoided in this type of system and it should never be allowed to exceed 20% of the full load value to avoid system failureÂ